Reproductive performance of African indigenous small ruminants under various management systems: A review - Wilson, R.T. (Elsevier, 1989)
Reviews the reproductive performance of African indigenous sheep and goats in different agro-ecological zones and under various management systems. Presents and discusses data on age at first parturition, litter size, the interval between successive parturitions annual reproductive rate, length of breeding life and effects of season on reproductive performance.